PENINGKATAN PEMAHAMAN PEMBELAJARAN PAI MATERI SHALAT MELALUI MEDIA GAMBAR KELAS IV SD NEGERI 0713 PIR TRANS SOSA I A TAHUN 2016 - Siti Holijah Ritonga (Universitas Muhammadiyah Tapanuli Selatan, 2017)
The background in this study is the lack of the use of learning media in a matter of prayer so that the learning achievement is less. The method used in this research is a class act. Collecting data in this study with observation and interview methods. In the data analysis, the authors used data reduction, data display, tentative conclusions and verification. Results of this research is student interest to learn the prayers in public primary schools Pir Trans Sosa 0713 I A after using media images has increased. In the pre-cycle to the first cycle students' interest increased by 92.6%. After using media images of student achievement Elementary School 0713 Trans Sosa Pir I A increased from the first cycle to the second cycle as much as 98.3%. Students who have not yet reached pre-cycle KKM on as many as 13 students and reaching the KKM many as 18 students. In siklusI students who have not reached the KKM as 6 students and has reached the KKM many as 25 students. In the second cycle students who have not achieved as much as 3 KKM KKM students and achieve as much as 29 students.